Comparison of Radiological Outcome in Anterior Cervical Discectomy and Fusion: Cage-Only v/s Cage and Plate Fixation - Abdul Razaque Mari, Qazi Muhammad Zeeshan, Muhammad Muzaffer Uddin, Farrukh Zulfiqar, Ramesh Kumar, Muhammad Munwar Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: A retrospective analysis of the outcome of anterior cervical discectomy and fusion comparing cage-only and cage-and-plate fixation on the basis of radiographic changes. Setting: In the department of Neurosurgery of a tertiary care hospital for two-year duration from January 2019 to December 2020. Methods: 56 patients who endured one-level ACDF (n = 34) and two-level ACDF (n = 22) for cervical disc disease were enrolled in the study and underwent a 12-months follow-up. Patients were separated according to cervical level and divided into cage-only group (ACDF-C) and cage-and-plate fixation group (ACDF-CP). The subsidence and status of fusion were evaluated on the radiography. Results: Comparing the ACDF-C with ACDF-CP at one level, the subsidence was detected in 50% of patients in the former group and in 33.3% of cases in the later at 12 months follow up. The two groups do not have statistically significant variance in terms of occurrence percentage (p = 0.32). In the two levels comparison of ACDF, ACDF-C had significantly more subsidence (75%) than the ACDF-CP group (28.5%; p= 0.046). The rate of fusion in single level ACDF of ACDF-C was not much different on statistics from that in the ACDF-CP group (87.5% and 88.8%, p= 0.43). The fusion was also similar in the two levels ACDF (ACDF-C= 87.5% and ACDF-CP= 92.8%; p= 0.30). Conclusions: This study’s radiological outcome did not exhibit any extra advantage of plate fixation compared to the cage-only in the 1-level ACDF subjects; however in ACDF at 2-level, a subsidence is much more probable without fixation of plate and therefore adding a plate to cage must be taken important.